High Speed Level-Down Shifter Using LTPO TFTs for Low Power and Interface Electronics - Sunaina Priyadarshi; Abidur Rahaman; Mohammad Masum Billah; Sabiqun Nahar; Md. Redowan Mahmud Arnob; Jin Jang (IEEE Journal of the Electron Devices Society)
This article intends to use a low-temperature poly-Si oxide (LTPO) level-down-shifter (LDS) to translate voltage signals with different amplitudes operating at various frequencies. The LTPO LDS is made of p-type low-temperature poly-Si and n-type a-InGaZnO thin-film transistors. The input voltage range of 2 V~10 V could be shifted to 1.2 V ~ 4.41 V output voltage. The rising and falling times are less than 400 ns at the operational frequency of 50 kHz. Also, the multiple output power supply of 6 V, 3 V, and 1.8 V for interface circuits has been possible with a single supply of 10 V. The proposed LDS shows a switching power consumption of 95.57 pW and area of 0.023 mm2.